METODE-METODE PENGOLAHAN AIR GAMBUT YANG EFEKTIF DALAM MENURUNKAN INTENSITAS WARNA AIR SUNGAI KAHAYAN: SYSTEMATIC LITERATURE REVIEW - Djinu, Lentar Aditya; Purnama, I Gede Herry (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021, 2022)
ABSTRACT Peat water is one of the surface waters found in peat areas that are scattered in the lowlands, such as in Sumatra and Kalimantan. The characteristic of peat water itself has a fairly high color intensity (brownish-red in color). Peat water is often used by the community for daily activities and has the risk of carrying diseases that can interfere with their health. The purpose of this study was to review and determine effective peat water treatment methods in reducing color intensity in research articles during the last decade. The Systematic Literature Review method used in this study, with literature sources found on the Google Scholar portal, Science Direct, and Garuda Ristekbrin. The search was carried out using the following keywords "water treatment", "reducing color intensity", "peat water", "water treatment", "reducing color intensity", and "peat water." After the article went through the review process, there were 16 articles and found different processing. Chemical processing using coagulation and flocculation processes, physical processing using a filtration process, and biological treatment with the addition of bacteria which can help the breakdown of organic substances in peat water. Minister of Health of the Republic of Indonesia Number 492 of 2010. The quality of watercolor at a maximum of 15 TCU. The most effective water treatment method to reduce color intensity chemically with color reduction efficiency reaches 99.20%. Keywords: Systematic Literature Review, Processing Method, Peat Water, Effective, Decreasing Color Intensity.